can anyone qive me the answer and explain how to work this question for future ref.

• Sep 18th 2009, 09:05 PM
tyonna
can anyone qive me the answer and explain how to work this question for future ref.
using the point-slope form of the line: y - y_1 = m(x - x_1) to find the equation of the line passing through the points (5, -3) and (-1, 5)
• Sep 18th 2009, 09:18 PM
Chris L T521
Quote:

Originally Posted by tyonna
using the point-slope form of the line: y - y_1 = m(x - x_1) to find the equation of the line passing through the points (5, -3) and (-1, 5)

First find the slope:

$m=\frac{y_2-y_1}{x_2-x_1}=\frac{5-(-3)}{-1-5}=\frac{8}{-6}=-\frac{4}{3}$.

Now plug $m$ and either point into $y-y_0=m\left(x-x_0\right)$ and that will give you the line you're looking for.

Can you try to finish this?
• Sep 18th 2009, 09:32 PM
tyonna
Quote:

Originally Posted by Chris L T521
First find the slope:

$m=\frac{y_2-y_1}{x_2-x_1}=\frac{5-(-3)}{-1-5}=\frac{8}{-6}=-\frac{4}{3}$.

Now plug $m$ and either point into $y-y_0=m\left(x-x_0\right)$ and that will give you the line you're looking for.

Can you try to finish this?

Not really, as what you just said was kind of a foreign language to me. Sorry
math is my worst subject!
• Sep 18th 2009, 11:49 PM
mr fantastic
Quote:

Originally Posted by tyonna
Not really, as what you just said was kind of a foreign language to me. Sorry
math is my worst subject!

If that is the case then you need to go back and thoroughly review the pre-requisite material that this topic assumes you know how to do.
• Sep 19th 2009, 12:57 AM
CaptainBlack
Quote:

Originally Posted by tyonna
using the point-slope form of the line: y - y_1 = m(x - x_1) to find the equation of the line passing through the points (5, -3) and (-1, 5)

See the PurpleMath article, you need the second worked example.

CB
• Sep 19th 2009, 05:24 AM
Viral
Oooh, I'd like to answer this as we just learned it yesterday :) .

To get the equation of a line passing through two points, you need to know how to work out the gradient:

$m = \frac {y_2 - y_1}{x_2 - x_1}$
or:
$m = \frac {y_1 - y_2}{x_1 - x_2}$

So to work that out with your question:

$m = \frac {y_1 - y_2}{x_2 - x_1} = \frac{-3 - 5}{5 - (-1)} = \frac{-8}{6} = -\frac{4}{3}$

So you now have the gradient, $-\frac{4}{3}$. Now choose one of the coordinates, I'll use $(5, -3)$.

$\begin{array}{rcrcrc}
y - y_1 = m(x - x_1)\\
y - (-3) = -\frac{4}{3}(x - 5)\\
3(y + 3) = -4(x - 5)\\
3y + 9 = -4x + 20\\
3y = -4x + 11\\
y = \frac{-4x + 11}{3}
\end{array}$

I've checked that against both of your coordinates and it works, so look over those notes and you should be able to understand it :) .